Kapabilitas Dinamis UMKM dalam Merespons Perubahan Lingkungan Bisnis - Liliani, Liliani; Wiliana, Jessy (UNUSA Press, 2018)
This study aims to explore the extent to which the SMEs are capable to develop dynamic capabilities to actively response changes of the environment. Exploration is conducted to SMEs in Surabaya engaged in food and beverage in order to capture the dynamics of the business environment and the ability of the SMEs relevant to dynamic capabilities. Three capabilities, namely adaptive, absorptive and innovative capabilities will be used to represent the elements of dynamic capabilities. This study uses qualitative descriptive approach to illustrate the abilities of SMEs infacing dynamic environment. Data collection uses semi-structured interview to four informants, who are chosen using purposive sampling method. The informants must meet all criteria set in this study to ensure their competence to explain SMEs operational activities, strategies and business environment. The results of this study shows that the SMEs have engaged in business activities related to adaptive, absorptive and innovative capabilities, but the activities are not managed comprehensively nor continuously. This study amplify important points of consideration to developdynamic capabilities in SMEs.